IMPLEMENTATION OF MODIFIED SCRIPT FOR LINUX BASED OPERATING SYSTEMS USING A LINEAR ALGORITHM FOR NETWORK PORT SCANNING : IMPLEMENTATION OF MODIFIED SCRIPT FOR LINUX BASED OPERATING SYSTEMS USING A LINEAR ALGORITHM FOR NETWORK PORT SCANNING - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The Python programming language has various module libraries for network scanning of hosts. In this paper the performance and implementation of a modified script for Linux based operating systems using a linear algorithm for network port scanning is presented.